Critical cultural competence of clinical nurses in China: A cross‐sectional survey. (25th March 2022) - Wang, Rong; Wu, Yuan Yuan; Duan, Gong Xiang; Liang, Cong; Tan, Lingling; Pu, Yucui; Dong, Le; Xu, Huilan
Abstract: Aim: To determine the level of critical cultural competence (CCC) among Chinese clinical nurses and explore its influencing factors. Background: Previous research has only focused on the theoretical model of CCC and the development of assessment tools; however, no large‐scale study has been conducted on the level of clinical nurses' CCC and its influencing factors. Method: Clinical nurses in 14 Level A tertiary hospitals ( n  = 3858) were surveyed using Almutairi's critical cultural competence scale (CCCS). Descriptive, univariate and multivariate analyses were performed. Results: The mean score of CCC was 4.44 ( SD  = 0.33). Critical empowerment ( M  = 4.85, SD  = 0.58) and critical awareness ( M  = 3.57, SD  = 0.99) had the highest and lowest scores, respectively. Female nurses, nurses in the nursing department and nurses with higher positions had higher CCC. Conclusion: The CCC of clinical nurses can be strengthened through targeted training, especially considering the fact that male and low‐ranking nurses who had the lower level of CCC work in different departments. Implications for Nursing Management: Hospital administrators should pay attention to the importance of culture and cultural differences among different countries or ethnic groups. Creating an equal and fair nursing environment and encouraging nurses to provide critical cultural nursing is important.